Nurcholish Madjid's Thoughts on the Modernization of Islamic Education: Its Relevance for the Development of Contemporary Islamic Schools - Solihah Titin Sumanti; Masysaroh Masysaroh (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to 1) analyze Nurcholish Madjid’s thoughts on the modernization of Islamic education, and 2) examine their relevance in developing contemporary Islamic schools. Madjid's concept integrates Islamic values with modern educational principles to create a system that is both adaptive and rooted in religious foundations. Methodology: This study employs a qualitative approach using a literature review method. Data were collected from Nurcholish Madjid’s writings, relevant Islamic education literature, and previous studies to provide a comprehensive analysis of his educational modernization framework. Main Findings: The findings indicate that Madjid’s thoughts on Islamic education modernization remain highly relevant today. His ideas advocate for an integrative curriculum, critical thinking-based pedagogy, and professional institutional management. Furthermore, his emphasis on rationality and openness in Islamic education supports a knowledge-based learning environment, enhancing both intellectual and spiritual development among students. Novelty/Originality of this study: This study highlights how Madjid's modernization framework contributes to contemporary Islamic education by bridging traditional religious teachings with modern educational methodologies. His ideas provide a foundation for developing Islamic schools that are globally competitive while maintaining their religious identity. This study also emphasizes the importance of transparency, accountability, and continuous educational reform in shaping a progressive Islamic education system.